Exploring Beneficial Properties of Haskap Berry Leaf Compounds for Gut Health Enhancement - Szymon Sip; Anna Sip; Piotr Szulc; Marek Selwet; Marcin Żarowski; Bogusław Czerny; Judyta Cielecka-Piontek (Antioxidants, 2024)
This study investigates the potential of formulated systems utilising haskap berry leaf extracts and dextran as carriers, to modulate both antioxidant and enzymatic inhibitory activities and their impact on the growth of specific bacterial strains. The analysis of antioxidant capacity, assessed through ABTS, CUPRAC, DPPH, and FRAP assays, revealed varying but consistently high levels across extracts, with Extract 3 (loganic acid: 2.974 mg/g, chlorogenic acid: 1.125 mg/g, caffeic acid: 0.083 mg/g, rutin: 1.137 mg/g, and quercetin: 1.501 mg/g) exhibiting the highest values (ABTS: 0.2447 mg/mL, CUPRAC: 0.3121 mg/mL, DPPH: 0.21001 mg/mL, and FRAP: 0.3411 mg/mL). Subsequent enzymatic inhibition assays demonstrated a notable inhibitory potential against α-glucosidase (1.4915 mg/mL, expressed as acarbose equivalent), hyaluronidase (0.2982 mg/mL, expressed as quercetin equivalent), and lipase (5.8715 µg/mL, expressed as orlistat equivalent). Further system development involved integration with dextran, showcasing their preserved bioactive compound content and emphasising their stability and potential bioactivity. Evaluation of the dextran systems’ impact on bacterial growth revealed a significant proliferation of beneficial strains, particularly the Bifidobacterium and lactobacilli genus (Bifidobacterium longum: 9.54 × 107 to 1.57 × 1010 CFU/mL and Ligilactobacillus salivarius: 1.36 × 109 to 1.62 × 1010 CFU/mL), suggesting their potential to modulate gut microbiota. These findings offer a foundation for exploring the therapeutic applications of haskap berry-based dextran systems in managing conditions like diabetes, emphasising the interconnected roles of antioxidant-rich botanical extracts and dextran formulations in promoting overall metabolic health.